GERMINATION, SEED VIGOR AND SEEDLING GROWTH OF CORN ON HIDRIC STRESS CONDITIONS - KAPPES, Claudinei; ANDRADE, João Antônio da Costa; HAGA, Kuniko Iwamoto; FERREIRA, João Paulo; ARF, Marcelo Valentini (Scientia Agraria, 2009)
The water availability and movement of water to the seeds are important for germination and seedling emergence, and these factors are influenced by soil water potential. Thus, this study was evaluated the germination, seed vigor and seedling growth of corn (XB 6010, XB 6012, XB 9003 and AG 9010) submited to hidric stress conditions. The seeds were sowing in paper towels moistened with mannitol solutions, using five levels of osmotic potential: 0.0 (control), -0.3, -0.6, -0.9 and -1.2 MPa. We evaluated the first count, and rate of germination, primary root length and shoot for shoot/root and fresh weight of seedlings. The average of hybrids were compared by Tukey test (P<0.05) and the mean levels of osmotic potential by regression analysis. Except for biomass of the seedling, there was an interaction between the factors for all tests, showing that the hybrids had a distinct behavior between them in relation to water stress induced by mannitol. Drought causes a reduction in the performance of hybrid seed corn, and they have behaved differently from each other as the tolerance in this condition. A reduction of germination, seed vigor and growth of maize seedlings as the osmotic potential of water becomes more negative